2026 Cattlemen's Day Full Report (Kansas Agricultural Experiment Station Research Reports, 2026)
This report includes research conducted in 2025 on beef cattle management, reproduction, nutrition, and meat science conducted at Kansas State University. Specific topics include effects of feeding techniques, herd health management, breeding, beef freezing methods and consumer preferences for meat color, grade, and cooking methods.
Keywords: beef cattle management; cattle nutrition; cattle reproduction; meat science